2018
DOI: 10.1177/0284185118805272
|View full text |Cite
|
Sign up to set email alerts
|

Apparent diffusion coefficients measured using different regions of interest in differentiating borderline from malignant ovarian tumors

Abstract: Background Apparent diffusion coefficients (ADCs) measured using different regions of interest (ROIs) are widely used in differentiating ovarian tumors. Purpose To evaluate the diagnostic performance of ADCs with different ROIs in differentiating borderline ovarian tumors (BOTs) from malignant ovarian tumors (MOTs). Material and Methods Thirty-five BOTs and 54 MOTs who underwent diffusion-weighted magnetic resonance imaging (MRI) were evaluated retrospectively. ADC values were independently measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Although we did not aim to make a differentiation between borderline and malignant tumors, a more detailed analysis of the signal could potentially show differences between those tumors which could also be scientifically relevant as well as of translational clinical benefit. In the current literature, there are few studies that address this topic and which are focused mostly on DWI parameters [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not aim to make a differentiation between borderline and malignant tumors, a more detailed analysis of the signal could potentially show differences between those tumors which could also be scientifically relevant as well as of translational clinical benefit. In the current literature, there are few studies that address this topic and which are focused mostly on DWI parameters [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative analysis of ADC maps in OC has previously shown promise in diagnostic and prognostic assessments, as well as in predicting NACT treatment response [ 17 , 23 , 26 29 ]. However, the integration of ADC measurements into clinical practice requires further research to define the most robust method for performing quantitative analyses in terms of performance and reproducibility, and to determine the optimal cut-off values for ADC change [ 18 , 25 , 30 ]. We retrospectively enrolled 23 patients with OC to examine whether the possible increase of ADC values could predict the response to NACT treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative recognition would enable strategies to retain fertility, e.g., cystectomies, ovarian stroma preservation, and unilateral salpingo-oophorectomy, therefore, DW-MRI has been explored as a potential clinical tool ( Figure 2 ). Various authors have investigated sophisticated ways to assess tiny solid components [ 39 , 40 , 41 ] including whole solid tumor histogram analysis models, diffusion kurtosis modelling, intravoxel incoherent motion models, or different non-Gaussian diffusion models. He et al excluded tumors with solid components smaller than 10 mm and carefully avoided hemorrhagic, necrotic, and cystic components and reported that diffusion kurtosis metrics (DKp10) yielded a sensitivity of 86% and an accuracy of 87% at a cut-off ADC value of 1.406 × 10 −3 mm 2 /s [ 42 ].…”
Section: Dw-mri For Differentiating Benign From Malignant Adnexal Massesmentioning
confidence: 99%